The Ḥadīth al-Ifk and the Contemporary Challenge of Hoaxes: A Study of Fakhruddin al-Razi’s Mafātīḥ al-Ghayb - Ahmad Baehaki; Muhammad Luthfi Mubarok (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2025)
This article explores the relevance of classical Qur’anic exegesis to contemporary challenges of misinformation, focusing on Fakhruddin al-Razi’s interpretation of Q.S. al-Nūr [24]:11–20 concerning the ḥadīth al-ifk the slander against Aisyah r.a. In Mafātīḥ al-Ghayb, al-Razi not only defends Aisyah’s honor but also constructs a moral and epistemological framework for assessing news and allegations. He differentiates between ordinary lies (kidhb), fabricated accusations (iftirā’), and ifk as a specific form of falsehood with greater psychological and social impact. Al-Razi criticizes the believers of his time for failing to uphold ethical standards when dealing with unverified information, highlighting the importance of ḥusn al-ẓann (positive presumption), tathabbut (verification), and bayyina (clear evidence) as Qur’anic imperatives. Through a thematic and analytical reading of al-Razi’s tafsir, this study argues that his exegetical approach combines theological depth, rational inquiry, and contextual awareness offering timeless ethical guidance. In the digital age, where hoaxes and slander proliferate rapidly, the ethical principles derived from al-Razi’s interpretation serve as a crucial reminder of Islam’s emphasis on justice, restraint, and the preservation of human dignity in all forms of communication. This study concludes that reviving Qur’anic ethics in dealing with information is vital for fostering an intellectually responsible and morally upright Muslim society in the face of modern challenges.